Save the radial: go distally - Chaddad, Rima; Rabah, Hussein; Awada, Batoul; Hmadeh, Malek (Journal of Cardiology and Cardiovascular Medicine, 2022)
Coronary artery disease is the leading cause of death worldwide. Percutaneous coronary intervention (PCI) is one of the most widely performed medical procedures used to save lives, currently over 3 million annually worldwide. The femoral artery has been the preferred vascular access site. However, radial access is gaining extensive popularity due to the benefits of earlier ambulation, fewer access site complications, and decreased rates of bleeding. Improvements in technology and understanding of the anatomic features of the vascular system have led to new insights into coronary angiography procedures. Distal radial access, which was first used in 2017, shows a higher success rate and fewer complications than previous sites; therefore, it might be the future for cardiovascular intervention. For this purpose, we conducted this prospective study at Beirut Cardiac Institute (BCI) comparing the two arms: radial vs. distal radial artery techniques through the anatomical snuffbox, in terms of patient’s length of stay, complication rate, and success rate of each procedure.